2000
DOI: 10.1084/jem.191.8.1423
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Restraint Stress Promotes Lymphocyte Apoptosis by Modulating Cd95 Expression

Abstract: Depending on the duration and severity, psychological tension and physical stress can enhance or suppress the immune system in both humans and animals. Although it is well established that stress alters the release of various hormones and neurotransmitters, the mechanisms by which stress affects immune responses remain elusive. We report here that mice subjected to chronic 12-hour daily physical restraint for two days exhibited a significant reduction in splenocytes, a process likely mediated by apoptosis as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
184
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 163 publications
(196 citation statements)
references
References 42 publications
(60 reference statements)
10
184
1
1
Order By: Relevance
“…Furthermore, endogenous opioids are known to be elevated by stress and to play a critical role in regulating stress-induced changes in the immune system (Kowalski, 1998). Opioid receptor antagonists Naltrexone and Naloxone also suppressed stress-induced reduction of splenocytes (Yin et al, 2000). The studies presented in this dissertation showed that OPN deficiency caused the same effects as these antagonists.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Furthermore, endogenous opioids are known to be elevated by stress and to play a critical role in regulating stress-induced changes in the immune system (Kowalski, 1998). Opioid receptor antagonists Naltrexone and Naloxone also suppressed stress-induced reduction of splenocytes (Yin et al, 2000). The studies presented in this dissertation showed that OPN deficiency caused the same effects as these antagonists.…”
Section: Discussionmentioning
confidence: 67%
“…It has been well documented that mice subjected to chronic physical stress exhibit an increased rate of lymphocyte apoptosis, redistribution of immune cells to the periphery and atrophy in the thymus and the spleen (Yin et al, 2000;Offner et al, 2006). Based on these observations, lymphoid organ atrophy is a convenient marker for monitoring stress-induced changes in the immune system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations